The Body of Woman and Woman’s Rights as Portrayed in Rupi Kaur’s milk and honey Based on Elaine Showalter’s Gynocriticism - Priska Tarigan; Martha Pardede; Siamir Marulafau (Journal of Language and Literature, 2021)
In the time of modern writing, women writers are increasingly free in raising the theme of their writing. Women are no longer reluctant to write things related to a woman’s body and it’s issue. This research aims to analyze the body of women and woman’s rights as portrayed in Rupi Kaur’s milk and honey (2014). This research belongs to library research that applied descriptive qualitative method with gynocriticism approach. Reading and selecting data techniques were used to collect the data. 28 poems raise the theme of the body of a woman and its issue used as the data in this research. To analyze the body of woman and woman’s rights in milk and honey,  gynocriticism theory by Ellaine Showalter were used. The result of the analysis shows that: 1) Woman’s body is described into three aspects, that is objectification of the body, owner of the body, and strength of the body. 2) There are three ways for a woman to embrace their rights. First, a woman is asked to be able to accept and acknowledge herself as she is. Second, a woman is expected to love and consider herself precious and equal to a man. Third, women must be able to help and to support other women in fighting for their rights.